Efektivitas Pembelajaran Kitab Safinatun Naja Melalui Metode Sorogan Studi Kasus di Pondok Pesantren Al-Fadhiilah Sukabumi - Sirulhaq, Sekarmaji; Ohan, Mohamad (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
Islamic boarding schools play an essential role in Islamic religious education in Indonesia. Traditional learning methods, especially the slogan method, are often used to improve students' understanding of the yellow classical books. This research uses a qualitative approach with a case study design at Al-Fadhiilah Islamic Boarding School. Data were obtained through interviews, observations, and documentation to analyze the effectiveness of the sorogan method in learning Safinatun Najah. The results showed that the slogan method effectively improved reading and understanding of the yellow classical book. Santri showed high enthusiasm and was able to interact actively with the ustadz, which contributed to their increased knowledge of the material.Â  The sorogan method has been proven to improve the academic skills of the santri and to build a closer relationship between the santri and the teacher. This study recommends applying the sorogan method in other pesantren to improve the quality of religious education.